1987
DOI: 10.1126/science.3563494
|View full text |Cite
|
Sign up to set email alerts
|

Answering Autobiographical Questions: The Impact of Memory and Inference on Surveys

Abstract: Survey questions often probe respondents for quantitative facts about events in their past: "During the last 2 weeks, on days when you drank liquor, about how many drinks did you have?" "During the past 12 months, how many visits did you make to a dentist?" "When did you last work at a full-time job?" are all examples from national surveys. Although questions like these make an implicit demand to remember and enumerate specific autobiographical episodes, respondents frequently have trouble complying because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
635
5
10

Year Published

1992
1992
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,004 publications
(670 citation statements)
references
References 36 publications
11
635
5
10
Order By: Relevance
“…Furthermore, unlike the development of excess adiposity, dieting and LOC eating both involve actively engaging in specific behaviors and the mean age of our sample was quite close to the reported onset ages of these investigated phenomena. Research has shown that time is related to the accuracy of recall because the more recently an event occurred (within the past 2-3 years), the easier it is to recall (Bradburn, Rips, & Shevell, 1987). Finally, our use of the semistructured interview format to query participants, a methodology recommended to enhance recall (Brewin et al, 1993), coupled with detailed probing to anchor children's recall to specific time frames (e.g., first dieting attempt and surrounding context), increases the likelihood that onset ages of these variables were accurately reported relative to one another.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, unlike the development of excess adiposity, dieting and LOC eating both involve actively engaging in specific behaviors and the mean age of our sample was quite close to the reported onset ages of these investigated phenomena. Research has shown that time is related to the accuracy of recall because the more recently an event occurred (within the past 2-3 years), the easier it is to recall (Bradburn, Rips, & Shevell, 1987). Finally, our use of the semistructured interview format to query participants, a methodology recommended to enhance recall (Brewin et al, 1993), coupled with detailed probing to anchor children's recall to specific time frames (e.g., first dieting attempt and surrounding context), increases the likelihood that onset ages of these variables were accurately reported relative to one another.…”
Section: Discussionmentioning
confidence: 99%
“…However, a retrospective design using a long follow-up period and self-reported data may have an increased chance of recall bias. 12,13 In addition, there were a large number of non-responders in which selective attrition/response could affect findings of the study. 14 Amatachaya et al 5 prospectively assessed falls over 6 months after discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Basically, the gambling becomes a necessity to access the environment's positive benefits (warmth, food, drink) rather than because the homeless person wants to 6 necessarily gamble. Furthermore, given the high proportion of homeless individuals that have alcohol and/or drug problems (as evidence above) there are also issues concerning their ability to competently complete 'paper and pencil' surveys given that the answering of questions relies on many facets of both long-term and short-term memory (Bradburn, Rips & Shevell, 1987;Presser, Couper, Lessler, et al, 2004). Therefore, high caution should be attached to data that may have been collected while the homeless person may have been in an intoxicating state due to alcohol and/or other drugs.…”
Section: Problem Gambling and Homelessness: Methodsological Problems Amentioning
confidence: 99%